CASE STUDY OF PHYSIOTHERAPY MANAGEMENT IN KNEE OSTEOARTHRITIS CONDITIONS - Amalia Solichati Rizqi; Putra, Yudha Wahyu; Wanito Ambarsari, dwi; Yunitasari, Rima (LPPM STIKes SATRIA BHAKTI NGANJUK, 2023)
Introduction Osteoarthritis knee is an idegenerative disease that usually occurs in the aging process. Physiotherapy is a part of health that usually handles cases of acne osteoarthritis. Purpose is to determine the effectiveness of physiotherapy management in knee osteoarthritis. method. The method used is a case study with a physiotherapy management approach for osteoarthritis cases. Patients underwent 6 interventions and were evaluated using a visual analogue scale and manual muscle testing. Results pain scores decreased from 6 to 3, muscle strength scores increased from 2 and 3 to 5. Conclusion Physiotherapy management in osteoarthritis of the knee is effective in reducing pain and increasing muscle strength